ANALISIS LINGKUNGAN PENGENDAPAN BERDASARKAN METODE GRANULOMETRI DAERAH FORMASI MAKATS, KOTA JAYAPURA, PROVINSI PAPUA - Evellyne Binsyowie Sandhiya Mandosir; Anabel, Anabel; Mellinda Ratna Pratamasari (Journal of Innovation Research and Knowledge, 2025)
His study aims to analyze the physical characteristics of sediments based on grain size and grain shape in order to interpret sediment provenance, transportation processes, and depositional environments. Granulometric analysis was carried out using the sieve analysis method with a series of graded sieves to obtain grain size distribution. The grain size data were then classified using the Wentworth Scale to identify sediment types and interpret the energy conditions of the depositional environment. In addition to grain size analysis, morphometric analysis was conducted by measuring the three main axes of sediment grains (length, width, and thickness) and determining grain roundness using the Powers Scale (1953) to infer transport distance and intensity. This research was conducted in the Puay and Abe Pantai areas, Jayapura, which were selected due to their diverse sediment types ranging from clay to pebble-sized materials. The results indicate that variations in grain size and grain shape reflect differences in energy conditions and depositional mechanisms at the study sites. Therefore, granulometric and morphometric analyses are effective methods for interpreting sedimentary processes and depositional environment characteristics in coastal areas.